The Architecture of a Lifetime: Structures of Remembrance and Invention in Walter Benjamin and Aldo Rossi - Jolien Paeleman (Footprint)
This article presents the result of research on the influence of Walter Benjamin’s thinking in the work of Italian architect Aldo Rossi (1931–1997). In present-day architectural criticism, Aldo Rossi’s oeuvre still constitutes a rich subject for discussion because of its resistance to easy pinpointing, even if Rossi himself explained his theories and methods of design on numerous occasions. In his writings, among these A Scientific Autobiography, Rossi quotes from a collection of Benjamin’s memoirs: Berlin Childhood around 1900. The architect believes that these short prose pieces express better than anything else what he himself had not been able to explain in his writing. In this paper I intend to show the poignancy of the words Rossi referred to and the implications they had on his architecture by offering close comparisons of Benjamin’s and Rossi’s autobiographical writings. In addition, this study examines how one of Rossi’s most famous architectural artefacts, the ossuary of San Cataldo cemetery at Modena, can be viewed as a coalescence of a Benjaminian thought-image, thereby fortifying the philosopher’s presence in modern architecture.